Risk factors for severe stunted among Children aged 2-5 years with stunting in Pontianak City, Indonesia - Suwarni, Linda; Selviana, Selviana; Vidyastuti, Vidyastuti; Abdullah, Asrul; Adi, Pranowo (GHMJ (Global Health Management Journal), 2023)
Background: Stunting is still a major public health in developing countries, including Indonesia. There are many predictors that might contribute to stunting, including child factors, mother factors, household factors, and community. This study focuses on children and mother level. Aims: This study aimed to examine the factors associated with severe stunted among children aged 2 to 5 years old. Methods: This study uses primary data in Pontianak City, Indonesia the data has been collected from January to February 2023. Respondents were selected by total sampling method. Univariate, bivariate, and multivariate have been done using STATA 17. Results: The analysis data revealed that 75.98% of children were stunted and 24.20 were severe stunted. The factors including low birth weight and birth interval were found significantly associated with severe stunted, other independent variables did not have a correlation for being severe stunted.  Conclusion: According to children's factors and maternal factors, the variables of low birth weight and birth interval were found to correlate with being severe stunted.